Synthesis of novel amphiphilic hyaluronan containing-aromatic fatty acids for fabrication of polymeric micelles - Matelová, Alena; Huerta-Angeles, Gloria; Šmejkalová, Daniela; Brůnová, Zdislava; Dušek, Jan; Vícha, Robert; Velebný, Vladimír (Carbohydrate polymers, 2016)
Novel hydrophobized hyaluronan (HA) derivatives, containing ω-phenylalkanoic acids (ω-PAA, 4-phenylbutyric acid, 6-phenylhexanoic, 8-phenyloctanoic or 11-tolylundecanoic acids) were prepared by esterification. Mixed anhydrides obtained after reaction of the carboxyl acid moiety and benzoyl chloride were found to be active acylating agents, affording hydrophobized HA in good yield and under mild conditions. The reactivity of the aromatic fatty acids towards esterification has decreased with the increasing length of the aliphatic spacer between the aromatic substituent and carboxylic acid moiety. The novel HA derivatives self-assembled from very low concentrations and were found to be non-cytotoxic. The potential use of ω-phenylalkanoic acids grafted-HA towards drug delivery applications was demonstrated by hydrophobic drugs (resveratrol and retinyl palmitate) encapsulation. The drug loading capacity of the novel HA derivatives was significantly improved most likely because of π⋯π interactions between the micelle core and loaded hydrophobic aromatic compound.
Keywords: hydrofobní a hydrofilní interakce; Benzoyl chloride (CID 7412); Retinyl palmitate (CID 5280531); buňky NIH 3T3; NIH 3T3 Cells; Topical application; Chemistry Techniques, Synthetic; micely; Fatty Acids; Amphiphilic polysaccharides; Mice; 4-Phenylbutanoic acid (CID 4775); Polymers; Hydrophobic and Hydrophilic Interactions; Resveratrol (CID 445154); kyselina hyaluronová; zvířata; Hyaluronic Acid; techniky syntetické chemie; viabilita buněk; Cell Survival; Micelles; myši; mastné kyseliny; polymery; Hyaluronan (CID 24728612); Hyaluronic acid; ω-Phenylalkanoic acids; Animals